Improve Numerical Literacy Through the Calistung Program in High School Students - Jogo, Hilarion; Wewe, Melkior; Bela, Maria Editha (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
This study aims to improve the literacy and numeration skills of the students through the calistung program. This research uses descriptive qualitative research methods and quantitative methods of research. The subjects of this study were high school students in grades 4, 5, and 6 at SDI Rawe. Data collection in this study is done through observation, interviews, and documentation. The qualitative approach is used to analyze and observe the program's application process, and the quantitative approach is used to measure the results of the program's implementation. The result of the application of the calistung program to the literacy and numeration skills of students is a change in the level of reading, writing, and counting skills that is demonstrated by the improvement of the final score from semester 1 to semester 2 as well as the acquisition of the AKM (pre-test & post-test) before and after the application.